Selected Recent Applications of Sparse Grids. Issue 1 (3rd March 2015) - Peherstorfer, Benjamin; Kowitz, Christoph; Pflüger, Dirk; Bungartz, Hans-Joachim
Abstract : Sparse grids have become a versatile tool for a vast range of applications reaching from interpolation and numerical quadrature to data-driven problems and uncertainty quantification. We review four selected real-world applications of sparse grids: financial product pricing with the Black-Scholes model, interactive exploration of simulation data with sparse-grid-based surrogate models, analysis of simulation data through sparse grid data mining methods, and stability investigations of plasma turbulence simulations.